Revising the slant column density retrieval of nitrogen dioxide observed by the Ozone Monitoring Instrument. Issue 11 (4th June 2015) - Marchenko, S.; Krotkov, N. A.; Lamsal, L. N.; Celarier, E. A.; Swartz, W. H.; Bucsela, E. J.
Abstract: Nitrogen dioxide retrievals from the Aura/Ozone Monitoring Instrument (OMI) have been used extensively over the past decade, particularly in the study of tropospheric air quality. Recent comparisons of OMI NO2 with independent data sets and models suggested that the OMI values of slant column density (SCD) and stratospheric vertical column density (VCD) in both the NASA OMNO2 and Royal Netherlands Meteorological Institute DOMINO products are too large, by around 10–40%. We describe a substantially revised spectral fitting algorithm, optimized for the OMI visible light spectrometer channel. The most important changes comprise a flexible adjustment of the instrumental wavelength shifts combined with iterative removal of the ring spectral features; the multistep removal of instrumental noise; iterative, sequential estimates of SCDs of the trace gases in the 402–465 nm range. These changes reduce OMI SCD(NO2 ) by 10–35%, bringing them much closer to SCDs retrieved from independent measurements and models. The revised SCDs, submitted to the stratosphere‐troposphere separation algorithm, give tropospheric VCDs ∼10–15% smaller in polluted regions, and up to ∼30% smaller in unpolluted areas. Although the revised algorithm has been optimized specifically for the OMI NO2 retrieval, our approach could be more broadly applicable. Key Points: We developed new NO2 fitting approach for the Aura Ozone Monitoring Instrument New fitting algorithm provides 10–35% lower NO2 slant column densities Both the stratospheric and tropospheric NO2 components are reduced